Serological evidence of foot-and-mouth disease virus infection in goat breeds in the Samsun province of Turkey - ALBAYRAK, H.; OZAN, E.; KADI, H.; CAVUNT, A.; TAMER, C.; TUTUNCU M, M. (Journal of the Hellenic Veterinary Medical Society, 2018)
Foot-and-mouth disease (FMD) is one of the major endemic trans-boundary livestock diseases of socio-economic importance in Turkey and worldwide. Goats constitute the third largest susceptible population of domestic livestock in Turkey. FMD surveillance and control strategies in the country largely ignore small ruminants, known to be critical in the epidemiology of the disease. In this study, blood samples were randomly collected from different domestic goat breeds (Anatolian black goat, Maltese and Saanen). The material consisted of 368 domestic goats, including 121 Anatolian black, 125 Maltese and 122 Saanen goats from Samsun province. The serum samples were examined for the presence of antibodies to foot and mouth disease virus using non structural proteins (NSPs) competitive enzyme-linked immunosorbent assay (ELISA). Out of 368 serum samples examined, 12 (3.26%) were positive for FMD. Seropositivity rates in Anatolian black, Saanen and Maltese breeds were 0.83%, 0.82% and 8.00% for FMD, respectively. Although, seropositivity rate in Maltese goat breed was higher than others, this result was not attributed to breed susceptibility. The results of the investigation indicate that FMD is less widespread in goats than sheep and cattle in Samsun province. The results, supported for the first time in Turkey the hypothesis that goats act as a potential reservoir of FMD virus and thus have a role in the epidemiology of FMD.